Answer:
The table that represents g(x) is
x g(x)
1 1
2 5
3 9
Explanation:
From the given information, we have that
f(x) = 2x - 3 and
g(x) = f(2x)
Then,
g(x) = f(2x) becomes
g(x) = f(2x) = 2(2x) -3
g(x) = 4x - 3
Now, we will put the values of x from 1 to 3 into the equation
When x = 1
g(x) = 4x - 3 becomes
g(x) = 4(1) - 3
g(x) = 4 - 3
g(x) = 1
When x = 2
g(x) = 4x - 3 becomes
g(x) = 4(2) - 3
g(x) = 8 - 3
g(x) = 5
When x = 3
g(x) = 4x - 3 becomes
g(x) = 4(3) - 3
g(x) = 12 - 3
g(x) = 9
Hence, the table that represents g(x) is
x g(x)
1 1
2 5
3 9